Borders, Mobility and Belonging. - Gilmartin, Mary (Policy Press shorts. Research., 2018)
Using cutting-edge academic work on migration and citizenship to address three themes central to current debates - borders and walls, mobility and travel, and belonging - the authors provide new insights into the politics of migration and citizenship in the UK and the US.